Meningkatkan Keterampilan Berpikir Kritis, Aktivitas, Hasil Belajar IPA Menggunakan Model PBL Berbasis Video - Irmayanti Wuryaningsih; Radiansyah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problems that occur in research are the low critical thinking skills, activities and student learning outcomes. This is because innovative models have not been used and appropriate learning media have not been used, such as digital media or learning video media. To overcome these problems, the Problem Based Learning (PBL) learning model is used combined with the TPACK approach based on video media. This study aims to describe teacher activities, student activities, and analyze critical thinking skills that have an impact on student learning outcomes. This study used Classroom Action Research (PTK), which involved 16 grade 5 students at SDN Kuin Selatan 1 Banjarmasin for the academic year 2022/2023. The results showed that the implementation of teacher activities in meetings 1 to 4 increased from 75% to 96% with very good criteria. Student activity increased significantly from 38% to 100% with very active criteria so that it affected increased student learning outcomes from meetings 1 to 4. It can be concluded that student learning activities on Theme 6 Heat and Transfer using the Problem Based Learning model, a combination of the media-based TPACK approach the video at SDN Kuin Selatan 1 Banjarmasin was declared successful and complete.